Answer:
42
Step-by-step explanation:
8+8+12+4+4+3+3
Something like this for the problem.
That the answer, I hope that will help you
Answer:
A) y = x^2 -1
B) -y = 2x^2 +1 We multiply B) by -1
B) y = -2x^2 -1
We can then say x^2 -1 = -2x^2 -1
3 x^2 = 0
x = 0
************* Double-Check: ******************
Equation A) y = -1 and
Equation B) y = -1
Step-by-step explanation:
Answer:
4/5
Step-by-step explanation:
8/15 = 8/15
3/5 = 9/15
2/3 = 10/15
11/15 = 11/15
We see that the pattern is that the terms increase by 1/15 as they move up.
Thus, the next term in the sequence is 12/15, which can be simplified to 4/5.
Let me know if this helps!
Answer:
Step-by-step explanation:
The graph that represents the function
f(x) = (x + 4)(x + 1)(x - 3)
crosses the x-axis three times: at x = -4, x = -1, and x = 3
because we apply the zero product rule and found the roots -4, -1, and 3
x+ 4= 0 → x = -4
x+1 = 0 → x = -1
x-3 = 0 → x = 3